MIDLIFE CRISIS AND CONFLICT IN JOHN UPDIKE’S “SEPARATING” - Khatun, Mst. Rokeya (Sanata Dharma University, Yogyakarta, 2025)
This paper analyzes midlife crisis and conflict, and their impact on familial relationships in John Updike's short story